Pengaruh Kontrol Diri terhadap Kecenderungan Adiksi Rokok pada Mahasiswa - Deava Oktaviani Hidayat; Calvina Izumi; Nada Izdihar Firdausa; Icha Diana Putri; Jingga Tsabitah; Sherly Nur Aliyah; Silvi Juwita (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2025)
College students, as a group of young adults, often face life transitions that involve academic, emotional, social, and economic pressures. One of the effects of these pressures is smoking behavior. According to pre-survey data, most college students who are active smokers consume 5-10 cigarettes per day. These students admitted to having tried to quit smoking at least once, but their efforts were unsuccessful, and they returned to their old habits. This difficulty indicates challenges in self-control. Participants in this study were active smokers across Indonesia, with a minimum consumption of 5–10 cigarettes per day. This study is quantitative in nature, using a self-control scale and a nicotine dependence scale to determine the absence of self-control influence on nicotine addiction. Data analysis in this study was conducted using simple linear regression analysis, yielding a p-value of 0.070 (>0.05). Therefore, it was concluded that self-control does not significantly influence addiction in the study sample.